Microseismic Response Characteristics Induced by Mining Activities: A Case Study - Xuesong Bai; Zhi Tang; Tao Zhao; Xiaoyang Cheng; Kai Chen (Advances in Civil Engineering)
For deep coal mines, geological disturbances or mining activities can cause damage to coal and rock masses, easily inducing dynamic disasters such as rock bursts or coal and gas outbursts, which seriously threaten the safety production of coal mine. In this paper, first, the Liyazhuang Coal Mine introduced the SOS MS (Sensor Observation Service Microseismic) monitoring system from the Polish Research Institute and verified the accuracy of its positioning. Then, to study the characteristics of MS signals induced by different mining activities, based on the field monitoring results, the waveform and frequency spectrum characteristics of MS signals at different energy levels induced by different mining activities are analyzed, and the energy levels of MS signals caused by different mining activities are classified. Studies have shown that there are large differences in the waveform and spectral characteristics of MS signals at different energy levels. High-level energy seismic signals are characterized by large amplitudes, low frequencies, relatively concentrated distribution, long vibration duration, and slow attenuation. In addition, the relationship between mining activities and MS events is also statistically analyzed based on the spatial and temporal distribution of MS events with the advancement of working face, and the results show that the increase of vibration frequency and energy can be precursor information for roof pressure. With the advance of the working face, the MS energy has the characteristic of periodic distribution, which is consistent with the periodic weighting revealed by the working resistance of the support. This study provides a reference for further revealing the energy release mechanism of rock burst.